Bentuk dan Fungsi Implikatur Pragmatik pada Pidato Kenegaraan Presiden Joko Widodo di Sidang Tahunan MPR RI Tahun 2024 - Maulana Danar Maalikih; Allika Fadiyah Hasna; Febri Adi Rusyanto (Pusat riset dan Inovasi Nasional, 2024)
Language in a state address functions not only as a medium for delivering information but also as a political communication tool rich in meaning and pragmatic strategies. This study describes the forms and functions of implicature found in President Joko Widodo’s State Address at the 2024 Annual Session of the People’s Consultative Assembly (MPR RI). The study focuses on two aspects: (1) the types of implicature, consisting of conventional and nonconventional implicatures, and (2) the functions of implicature, including assertive, directive, expressive, and commissive functions. The research employs a descriptive qualitative method with a pragmatic approach and content analysis. The data, in the form of utterances containing implied meanings, were collected using the listening and note-taking techniques and analyzed based on Grice’s implicature theory and relevant pragmatic frameworks. The results show that President Joko Widodo’s state address contains two types of implicature: conventional implicature, which carries explicit and commonly understood meanings, and nonconventional implicature, which requires contextual interpretation because of its implicit nature. Furthermore, four functions of implicature were identified: (1) assertive, used to express facts and the speaker’s beliefs; (2) directive, containing appeals and encouragement to continue national development; (3) expressive, conveying gratitude and appreciation to national institutions; and (4) commissive, emphasizing the President’s commitment to maintaining international trust and national sovereignty. Overall, the findings reveal that the use of implicature in the state address serves as an effective and polite political communication strategy.